The Importance of Islamic Educational Values in The Arts of Tembang Gambuh or Tembang Macapat - Alfi Zidanurrohim; Olvy Mailandari; Yazidah Ichsan; M. Afif Nur Tajuddin; Eviana Agustin (Raudhatun Najah Publisher, 2022)
This study aims to investigate the value of Islamic education in gambuh songs, as well as the effects gambuh songs have on Islamic education. Gambuh songs are part of the mocopat song, a walisongo tool for spreading Islam, especially in Java. Tembang gambuh had artistic value to attract the attention of the people at that time who were very open to art; from its entertainment value, the trustees also inserted scientific and Islamic values ​​into it. This type of research is qualitative, with a literature review, descriptive analysis, and content analysis, namely scientific analysis based on communication messages. They begin with the data analysis process by interpreting the Javanese language as the content of the song Gambuh. Research findings; the gambuh song lyrics contain messages for proper behavior and behavior that is reluctant to accept advice. Someone without guidance and direction in life will be perverted. There is a relationship between cultural products (tembang gambuh) and religious values. The value of this tembang gambuh song can be used as a guide and a guide for life in society.